2021
DOI: 10.1155/2021/6675785
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Crash Injury Severity Control from Novice and Experienced Drivers: A Bivariate Random-Effects Probit Analysis

Abstract: This study intended to investigate the crash injury severity from the insights of the novice and experienced drivers. To achieve this objective, a bivariate panel data probit model was initially proposed to account for the correlation between both time-specific and individual-specific error terms. The geocrash data of Las Vegas metropolitan area from 2014 to 2017 were collected. In order to estimate two (seemingly unrelated) nonlinear processes and to control for interrelations between the unobservables, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The risk of fatal accident is increased for young novice drivers and decreased for old novice drivers. This is consistent with Xiao’s study [ 4 ]. They found that increasing age reduces the risk of fatal accidents for novice drivers.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The risk of fatal accident is increased for young novice drivers and decreased for old novice drivers. This is consistent with Xiao’s study [ 4 ]. They found that increasing age reduces the risk of fatal accidents for novice drivers.…”
Section: Resultssupporting
confidence: 94%
“…By analyzing the eye movement data of novice and experienced drivers when driving on different types of roads, Underwood et al [ 14 ] found that compared with novice drivers, experienced drivers showed higher sensitivity on the whole. Xiao et al [ 4 ] used the bivariate random-effects probit model to analyze the influencing factors of accident severity for novice and experienced drivers, and they found that the key factors of fatal injury suffered by novice drivers and experienced drivers are different.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the evolution of the electronic and information technology, many advanced techniques can be applied to the intelligent vehicles, such as autonomous emergency braking and electronic stabilization programs (ESP), to enhance the safety issue. Thus, the vehicle quality can be improved and safety issue can be guaranteed, and then the traffic accident can be reduced (Liu et al, 2020;Xiao et al, 2021;Xu et al, 2020;Lyckegaard et al, 2015). Electric vehicle (EV), which has lower carbon emission, is an important industry in the world.…”
Section: Introductionmentioning
confidence: 99%